PENGARUH MEDIA KOMIK SAINS BERBASIS KARAKTER TERHADAP MINAT BACA DAN HASIL BELAJAR MAHASISWA PENDIDIKAN IPA - Ani Widyawati; Astuti Wijayanti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2019)
This research is a quasi-experimental type Nonequivalent Control Group Design which aims to determine the effect of the use of learning media in the form of character-based science comics on reading interest and learning outcomes of science education program students in science 2 subjects. This study uses learning media containing science material integrated with character education in it is very necessary for the present and future eras. This is in line with the 2013 revised curriculum demands of 2017 which aim to build the 2045 generation with strong character, possess 21st-century skills with HOTS assessment, and literacy. Data collection techniques using questionnaires and tests. The results of this study indicate that there is a significant influence on the use of comic media in learning in science courses 2 addictive and psychotropic substances on learning outcomes and student interest in reading. This is evidenced by the results of the significance of the "t" test for post-testing learning outcomes and reading interest between the experimental class and the control class valued at 0,000 or less than 0.05 (Î±). The results of the gain test which shows that the difference in posttest learning outcomes of natural science students in Natural Sciences 2 course is in the high category while for reading interest is in the medium category.